GERAKAN PERLAWANAN IDEOLOGI PATRIARKI DI BALI DALAM KARYA SASTRA OKA RUSMINI TAHUN 2000-2012 - Dewi, Intan Sri; Erviantono, Tedi; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2017)
Women struggled so long to be able to have equal rights with men. The process of struggle continues into a movement. The majority of contemporary movements do not have a clear structural basis and not always through group mobilization, one of them through cultural productssuch as literary works by Oka Rusmini that tell about how Balinese women wrestle with the struggle to get equal rights with men in the middle of patriarchal tradition. The purpose of research is to know the resistance movement of patriarchal ideological in Bali in Oka Rusmini’s literary works 2000-2012. This research uses New Social Movement Theory and qualitative method of analysis. The findings of this research that the resistance movement by Oka Rusmini meets the criteria as a new social movement and is an movement that fight for women's issues through non-conventional political channels. This movement, firstly, affirmed by Oka Rusmini that her literature works is a resistance movement, second, according to semiotic analysis by Barthes that Oka Rusmini’s literature works is laden of resistance to patriarchy. Overall, Oka Rusmini’s literature works succeeded in influencing public opinion, making some new thinking, and getting political influence from the government . Keywords: Resistance Movement, Patriarchy, Literature